2017
DOI: 10.3347/kjp.2017.55.5.555
|View full text |Cite
|
Sign up to set email alerts
|

Chigger Mite (Acari: Trombiculidae) Survey of Rodents in Shandong Province, Northern China

Abstract: Chigger mites are parasites of rodents and other vertebrates, invertebrates, and other arthropods, and are the only vectors of scrub typhus, in addition to other zoonoses. Therefore, investigating their distribution, diversity, and seasonal abundance is important for public health. Rodent surveillance was conducted at 6 districts in Shandong Province, northern China (114–112°E, 34–38°N), from January to December 2011. Overall, 225/286 (78.7%) rodents captured were infested with chigger mites. A total of 451 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Approximately 3,000 species of chigger mites have been recorded worldwide, 61 of which are recorded in the Korean Peninsula (Lee ; Huang et al . ). Among these, Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 3,000 species of chigger mites have been recorded worldwide, 61 of which are recorded in the Korean Peninsula (Lee ; Huang et al . ). Among these, Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 97%
“…Among the vectors being monitored are the chigger mites (Acarina:Trombiculidae), whose larval stage are a vector for bacteria that cause Tsutsugamushi disease (obligate intracellular bacterium Orientia tsutsugamushi [Rickettsiales: Rickettsiaceae]) (Traub & Wisseman 1974). Approximately 3,000 species of chigger mites have been recorded worldwide, 61 of which are recorded in the Korean Peninsula (Lee 2006;Huang et al 2017). Among these, Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Second, rodents and Leptotrombidium scutellare as the main reservoir host and transmission vector for Orientia tsutsugamushi in Shandong Province. Their density fluctuations are closely related to the seasonal distribution of scrub typhus cases, and the monthly distribution of scrub typhus cases was consistent with the fluctuation of Leptotrombidium scutellare[9, 30, 31]. Third, some studies have shown that meteorological factors affect the incidence of scrub typhus, such as temperature, sunlight, precipitation, etc[16, 32, 33].…”
Section: Discussionmentioning
confidence: 70%
“…Endemic typhus is caused by Ricettsia mooseri and is mainly transmitted by Xenopsyllae cheopis, rodents are their natural hosts. Scrub typhus is caused by the intracellular pathogen Orientia tsutsugamushi and is transmitted by chigger mites[9]. We describe the magnitude and distribution of these diseases in Shandong Province based on the notifiable reporting date, focusing on three-dimensional distribution from 2009 to 2017 and characteristic of SFTS fatality.…”
Section: Introductionmentioning
confidence: 99%
“…Trombiculiasis is an infestation caused by various types of chiggers. Chiggers refer to larval stage of mites belonging to subgroup of the class Arachnida, family Trombiculidae and Leeuwenhoekiidae . Up to 3,000 chigger mite species that parasitize mammals (especially rodents), reptiles, birds, amphibians, and invertebrates have been reported worldwide.…”
mentioning
confidence: 99%